LEXICAL RICHNESS AND SYNTACTIC COMPLEXITY OF THE ENGLISH EXAM PAPERS OF SBMPTN - WINDY ARDIANITA SARI, 121714253012 (2019)
This study aims to investigate the lexical richness and syntactic complexity of English exam papers of SBMPTN from 2009 to 2018 consisting of ten papers with 19.335 tokens. The data were analyzed by using several tools: AntConc, AntWord Profiler, Vocabprofiler, Claws Tagger, and L2 Syntactic Complexity Analyzer. Lexical richness involves lexical originality, lexical density, lexical sophistication, and lexical variation proposed by Laufer and Nation (1995). This study found that the most original English exam papers of SBMPTN is in 2010. In the lexical density findings, the writer found out that the densest lexical items existed in the year 2010 with the value 0.54. For the lexical sophistication, the writer figured out that several English exam papers of SBMPTN such as in the year 2016 and 2018 has exceeded the percent token of AWL 9% based on Coxhead’s theory. In lexical variation, the English exam papers of SBMPTN which have the most lexical variation is in the year 2010 and 2013. For the syntactic complexity consisting of length of production unit, the amount of subordination, the amount of coordination, and the degree of phrasal sophistication, this study almost has the level of complexity as college-level English writing and undergraduate research articles. This study is expected to give broader knowledge to the reader as well as a critic to the test makers in order to give more attention to the lexical richness and syntactic complexity in composing the next English exam papers of SBMPTN.